2020
DOI: 10.1038/s41419-020-2334-2
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis driven by radical oxidation of n-6 polyunsaturated fatty acids mediates acetaminophen-induced acute liver failure

Abstract: Acetaminophen (APAP) overdose is a common cause of drug-induced acute liver failure. Although hepatocyte cell death is considered to be the critical event in APAP-induced hepatotoxicity, the underlying mechanism remains unclear. Ferroptosis is a newly discovered type of cell death that is caused by a loss of cellular redox homeostasis. As glutathione (GSH) depletion triggers APAP-induced hepatotoxicity, we investigated the role of ferroptosis in a murine model of APAP-induced acute liver failure. APAP-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
173
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(181 citation statements)
references
References 51 publications
6
173
1
1
Order By: Relevance
“…Lipid metabolism is closely linked to the regulation of ferroptosis. The accumulation of lipid peroxidation seems to be a key process in the execution phase, in which PUFAs play an important role ( Stockwell et al, 2017 ; Wenzel et al, 2017 ; Yamada et al, 2020 ). Usually, free PUFAs, especially AA and AdA are esterified to membrane phospholipids [mainly PUFA-containing phosphatidylethanolamines (PEs)].…”
Section: Discovery and Mechanisms Of Ferroptosismentioning
confidence: 99%
“…Lipid metabolism is closely linked to the regulation of ferroptosis. The accumulation of lipid peroxidation seems to be a key process in the execution phase, in which PUFAs play an important role ( Stockwell et al, 2017 ; Wenzel et al, 2017 ; Yamada et al, 2020 ). Usually, free PUFAs, especially AA and AdA are esterified to membrane phospholipids [mainly PUFA-containing phosphatidylethanolamines (PEs)].…”
Section: Discovery and Mechanisms Of Ferroptosismentioning
confidence: 99%
“…It is now well-accepted that APAP can induce hepatoxicity through two common forms of cell death, namely apoptosis and necrosis 4 . Notably and intriguingly, a recent study indicated that the third form of cell death, termed ferroptosis, might also contribute to APAP-induced DILI in vitro 5,6 . However, in-depth studies are required to define the key role of ferroptosis in DILI, which will open a new door for developing effective intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…NAPQI binds to GSH and leads to severe depletion of GSH in hepatocytes [ 56 ]. Yamada’s team has recently found that ferroptosis driven by ω-6 PUFAs is associated with acetaminophen-induced ALD [ 57 ]. Besides, ferrostatin-1, DFO and vitamin E could exert a protective effect on hepatocytes by suppressing lipid peroxidation and GSH depletion [ 57 ].…”
Section: Ferroptosis In Liver Diseasesmentioning
confidence: 99%
“…Yamada’s team has recently found that ferroptosis driven by ω-6 PUFAs is associated with acetaminophen-induced ALD [ 57 ]. Besides, ferrostatin-1, DFO and vitamin E could exert a protective effect on hepatocytes by suppressing lipid peroxidation and GSH depletion [ 57 ]. Moreover, it was recently shown using CRISPR-Cas9 that cytochrome P450 oxidoreductase, which is directly implied in the detoxification of xenobiotics by hemoprotein, was necessary for ferroptotic cell death by upregulating the PUFAs peroxidation [ 58 ].…”
Section: Ferroptosis In Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation